Pengaruh Paparan Audio Gelombang Alpha terhadap Transformasi Emosional Sebelum Ujian Modul - I. Manahampi, Janly; F. Rumampuk, Jimmy; E. W. Moningka, Maya; Lintong, Fransiska; R. Danes, Vennetia (Green Publisher Indonesia, 2025)
Academic stress has become a significant issue among students worldwide, with a high prevalence rate, particularly before exams. According to the Global Burden of Disease Study (2020), mental disorders, including stress, affect 1 in 4 people globally. In Southeast Asia, around 45% of students experience significant levels of stress, while in Indonesia, the prevalence ranges from 36.7% to 71.6%. This academic stress can impact academic performance, reduce concentration, cognitive function, and memory. Female students, in particular, are more vulnerable to academic stress due to hormonal changes that affect emotional stability. Although various non-pharmacological approaches, such as mindfulness and exercise, have proven effective, both require a significant time commitment. As an alternative, exposure to alpha wave audio has emerged as an interesting option, as it can help regulate emotions and reduce stress levels. The aim of this study is to determine the effect of exposure to alpha wave audio on emotional transformation before module exams in female students of the 2022 cohort at the Faculty of Medicine, Sam Ratulangi University. This study uses an quasi experimental research design with a one-group pre-test post-test design, comparing measurements before and after the intervention. The data is then analyzed using the non-parametric Wilcoxon test. A comparison of emotional changes before and after listening to alpha wave audio was measured in 100 subjects in the intervention group. The results showed significant changes in both positive and negative emotions, with a significance value of 0.028 (p<0.05). This study concluded that there is an effect of alpha wave audio exposure on emotional transformation before the module exam.